THE INFLUENCE OF COMMUNICATION AND COMPENSATION TOWARD SPIRIT AT WORK OF UNIVERSITAS NEGERI JAKARTA LECTURER - Tanacha P. Sianturi, Immanuel; Maria Silaen, Sondang (Dinasti International Journal of Digital Business Management, 2021)
The purpose of this research are: 1) to know job description of compensation and spirit at work of lecturer of Faculty of Economics, Universitas Negeri Jakarta, 2) to know the influence of communication to spirit at work of lecturer of Faculty of Economics, Universitas Negeri Jakarta; 3) to know the effect of compensation On spirit at work of lecturer of Faculty of Economics, Universitas Negeri Jakarta, 4) to know communication and compensation can predict increase of spirit at work of lecturer of Faculty of Economics, Universitas Negeri Jakarta. The research model used in this research is regression analysis. This research will be conducted on 67 lecturers of Faculty of Economics, Universitas Negeri Jakarta. This research uses descriptive and explanatory analysis. Data collection techniques using SPSS statistical application program version 22.0 The results in this study are: 1) compensation has a positive and significant impact on spirit at work of FE UNJ lecturers. 2) the communication has a positive and significant impact on the spirit at work of FE UNJ lecturer. 3) the result of model feasibility test shows that communication and compensation can predict spirit at work of FE UNJ lecturer.